(untitled) (Journal of the College of Languages (JCL), 2021)
With the advancement of technology ,the study of cross-cultural communication via on line has become an important and researchable topic in linguistic theory and its applications.The aims of this study are two- fold (a) exploring the influence of cultural diversity on on-line interaction between American native speakers (NSs) and Iraqi non-native speakers (NNSs) of English which, together with other factors might potentially lead to what Thomas(1983) calls "pragmatic failure" (PF), a main cause of communication breakdowns and (b) specifying which type of PF occurs more frequently between the two groups along with the reasons behind such failures. To achieve these objectives , a number of online chats conducted between (10) American speakers of English and (8) Iraqi graduate students of English were collected and analyzed on the basis of Thomas’ (1983) division of PF in an attempt to verify the assumption that pragmatic failure is a result of cultural diversity between the two groups of participants.Results revealed that the cultural differences between the two groups could be a major cause of misunderstanding ie. PF., a finding which can be of value to textbook designers and teachers of English as a foreign language (FL)who are required to improve students’ pragmatic ability in classroom by focusing not only on their grammatical competence but also on their pragmatic competence.